Facing COVID-19: Early Recognition and Triage Tool for Medical Treatment Facilities With Limited Resources. Issue 1 (30th January 2021) - Jänig, Christoph; Gurney, Jennifer M; Froklage, Roger; Groth, Robin; Wirth, Christine; van de Krol, Hendrik; Schmidbauer, Willi; Güsgen, Christoph
ABSTRACT: Introduction: Coronavirus Disease 2019 (COVID-19) is spreading all over the world. Health systems around the globe have to deal with decreased capabilities and exhausted resources because of the surge of patients. The need to identify COVID-19 patients to achieve a timely opportunity to treat and isolate them is an ongoing challenge for health care professionals everywhere. A lack of testing capabilities forces clinicians to make the crucial initial decision on the basis of clinical findings and routine diagnostic laboratory test. This article reviews the current literature and presents a new adapted protocol for diagnosing and triaging COVID-19 patients. A special emphasis lies on the stepwise approach guiding the medical provider to a triage decision that is suitable for the individual patient and the situation of the local medical treatment facility. Materials and Methods: On March 30, 2020, a PubMed based literature research on COVID-19 following the preferred reporting items for systematic reviews and meta-analyses guidelines was performed. A diagnostic and triage tool for COVID-19 was designed based on the major findings in the reviewed literature. Results: After a selection process, focusing on the topics "epidemiology, " "clinical characteristics, " and "diagnostic tools, " 119 out of a total amount of 1, 241 publications were selected to get an overview of the growing evidence. Conclusions: The designed Early Recognition and Triage Tool enables the medical provider to use the applicable modules of the protocol for capabilities of the local setting to get the most appropriate diagnostic and triage done. The tool should give guidance for the initial approach until specific testing for the COVID-19 virus is available.